India in search of glory : Political calculus and economy - Lahiri, Ashok K. (New Delhi : Penguin, 2022)
India and the Indians have made some progress in 75 years after Independence. The number of literates has gone up. The Indians have become healthier and their life expectancy at birth has gone up. The proportion of people below the poverty line has also halved. But the shine from the story fades when India is compared with that of the East Asian Tigers and China. It looks good but not good enough. India looks far away from the glory it seeks. This issue forms the core subject matter of this book. It tries to argue why India could not achieve more and what all it could have achieved. It paints a picture of its possible future and highlights the areas that need immediate attention.
Keywords: Politics & State; India -- History -- 1947- -- Politics and government; Political Science / Public Policy / Economic Policy